2018
DOI: 10.1016/j.jped.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

BH4 deficiency identified in a neonatal screening program for hyperphenylalaninemia

Abstract: The prevalence of BH deficiencies in Minas Gerais was slightly higher than that found in the literature, but the frequency among hyperphenylalaninemias was similar. Although rare, they are severe diseases and, if left untreated, lead to developmental delays, abnormal movements, seizures, and premature death. Early treatment onset (starting before 5 months of age) showed good results in preventing intellectual disability, justifying the screening of these deficiencies in newborns with hyperphenylalaninemia iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
0
10
1
Order By: Relevance
“…1) Phenylketonuria (PKU) is an inborn error of amino acid metabo lism caused by phenylalanine hydroxylase gene mutations. 2,3) PKU patients experience an irreversible decrease in intelligence quotient scores, suppressed verbal function, impaired attention, and underdeveloped motor control skills. 4,5) The early diagnosis of PKU before the end of the first month of life is critical to controlling hyperphenylalaninemia.…”
Section: Global Prevalence Of Classic Phenylketonuria Based On Neonatmentioning
confidence: 99%
“…1) Phenylketonuria (PKU) is an inborn error of amino acid metabo lism caused by phenylalanine hydroxylase gene mutations. 2,3) PKU patients experience an irreversible decrease in intelligence quotient scores, suppressed verbal function, impaired attention, and underdeveloped motor control skills. 4,5) The early diagnosis of PKU before the end of the first month of life is critical to controlling hyperphenylalaninemia.…”
Section: Global Prevalence Of Classic Phenylketonuria Based On Neonatmentioning
confidence: 99%
“…Testing for HPA is included in neonatal screening in most parts of the world. Because early and regular treatment for HPA is correlated with better prognosis [ 9 , 17 ], patients should be diagnosed and treated as soon as possible. In our study, we found that the primary treatment time was within 1 month after birth.…”
Section: Discussionmentioning
confidence: 99%
“…Data from 2018 to 2019 from DATASUS, the informatics department of the SUS [ 14 ], demonstrates that 6,495 diagnostic procedures for RD were performed by the first five RDRS that presented production data. Considering that the more robust RDRS attend approximately 1000 patients per year, and the others 500 patients per year, a sample number of approximately 55,000 individuals is estimated.…”
Section: Plans and Goalsmentioning
confidence: 99%